Imagology and Transnacionalism: Stereotypes. Hetero-imagotypes and Allophilia in Rhys Hughes and João de Melo - Simões, Maria João (2018)
Intercultural communication and the way we perceive foreigners are crucial concerns in contemporary society.Throughout History, and in several ways, Literature has provided us with vivid representations of foreign and national characters, in their frequent cultural clashes, helping us to better understand humanity. This paper aims at identifying the importance of Imagology inside the literary criticism domain as an adequate hermeneutical approach to better understand hetero-images and auto-images represented in literary texts. It also claims that recent research on stereotypes achieved in Social Psychology will vastly contribute to the analysis of the images and counter-images represented in literary works, as I have pointed out in the “Xenographies” - Wolverhampton Conference, in 2009, and in the introduction of the book Imagotipos Literários (2011). Philippe Beck also noted, in 2010, the vicinity of stereotypes study and the construction of self and hetero-images, and advocated the idea of conjoint and interdisciplinary research.